The financialization of remittances in Nepal: Governing through the pedagogy of fear and hope - Lekh Nath Paudel; Rahel Kunz (Finance and Society, 2022)
In the last decade, remittances have become connected to financialization, expanding financial markets and deepening financial logics in what has been termed the financialization of remittances (FOR). In Nepal, where remittances are of key importance, this manifests itself in the country's development strategy through attempts to formalize remittances and promote financial inclusion, entrepreneurship, and financial infrastructure. This article focuses on the most salient manifestation of the FOR in Nepal: a large-scale financial literacy education (FLE) campaign for transnational families. To examine how this FOR-FLE complex works, we bring together insights on emotional governance with those on the creation of (gendered) financial subjectivities. Based on an analysis of FLE pedagogical material and interviews with FLE experts, we suggest that the FOR-FLE complex in Nepal mobilizes a pedagogy of fear and hope to discipline the financial behavior of transnational families, transforming them into self- governing miniature financial corporations. We also highlight the gender dimensions of this emotional regime, which creates terror and works to patronize, shame, and stigmatize non- migrant women of transnational families, rendering them responsible for development, decreasing out-migration, and reducing the economy's import dependency.
Keywords: 300; Remittances; financialization; financial literacy education; financial subjectivities; emotional regime; heteronormativity